Case Reports : Melioidosis of head and neck in Sawanpracharak hospital - จิราวัฒนอนันต์, สาวิตรี (Thai Journal of Otolaryngology Head and Neck Surgery, 2021)
Melioidosis is a common bacterial infection in Southeast Asia and Northern Australia. In Thailand , it is a common disease in Northeast region1,2,3, as reported incidence 4.4 per 100,000. In 2019, data from Nakhon Sawan Provincial Public Health Office shows 5 reported cases of melioidosis (0.49:100,000) and 1 reported case of death (0.1 :100,000)4. The presentations were fever, sepsis, pneumonia, abscess, infectious arthritis, urinary tract infections, sialadenitis and organ failure2,3,5. Burkholderia pseudomallei can enter the body through the intact skin in case of prolonged exposure to soil or water. The other routes of infection were fecal-oral route , 3,5,6, The diagnosis was confirmed by positive culture 7,8 The treatments were surgical, medical treatments. The ceftazidime infusion and switch therapy to cotrimoxazole with or without doxycycline for 3-6 months is the treatment of choice to prevent recurrence 7,8,9. This case report are the 2 cases melioidosis of Head and Neck in 2019. There two cases were confirmed with pus culture .